Influence of Perceived CSR on Purchase Intention in Malaysia Vegan Food Industry - Pin, Lim Wee; Kumar, Kavigtha Mohan (Journal of Entrepreneurship, Business and Economics, 2026)
This study aims to fill the gap in the study of the relationship between CSR perception and purchase intention in vegan food products within the context of Malaysia, a developing country known for its multiracial and multicultural community. This study aims to give Malaysian food industry players and entrepreneurs an insight into the implications of CSR perception towards Malaysian consumers on vegan food products. The population of this study consists of general consumers in Malaysia. As a cross-sectional study was carried out, the responses across different consumer demographic profiles were analysed to further understand the customers with various backgrounds. This study was conducted in a quantitative research mode. A cross-sectional survey was carried out, and data were collected from 99 Malaysian consumers with different demographic profiles. The survey data was analysed by adopting the PLS-SEM model. The result concluded that perceived CSR do not directly affect the purchase intention of vegan food, but is mediated by satisfaction and price fairness. Health consciousness does not have a significant effect towards the purchase intention of vegan food. Food companies must develop a strategy to link CSR initiatives with delivering satisfaction and price fairness value to consumers, thereby attracting purchase intention. Strategies and action plans must be implemented to emphasise the importance of dietary control in forming a healthier community. Effort from the government and food companies plays vital roles in raising awareness and encouraging Malaysians' access to affordable, healthy vegan food. This article's contribution is to propose a model that broadens the research in the literature examining the association between "Perceived CSR" and "Purchase intention" for vegan food products. The current study is an addition to the literature in that it analyses the acceptance of Malaysian consumers of vegan food products with different factors as mediators. Research Paper Keywords: Perceived CSR, Purchase Intention, Satisfaction, Price Fairness, Health Consciousness, Vegan Food Reference to this paper should be made as follows: Pin, L.W., & Kumar, K.A.M. (2025). Influence of Perceived CSR on Purchase Intention in Malaysia Vegan Food Industry,   Journal of Entrepreneurship, Business and Economics , 13 (2), 188–219.